How well does a cash-flow tax on wages approximate an economic income tax on labor income? - Martin Weiss (Arbeitskreis Quantitative Steuerlehre (arqus), 2007)
The recent German discussion has witnessed increasing interest in the Dual Income Tax. The analysis of its merits, as opposed to those of a comprehensive income tax, is usually conducted with the main argument of the increasing mobility of financial capital in mind. This article pursues an alternative route of reasoning, arguing that the composition of the tax base of labor income entails a differentiation of the tax rates on capital and labor income. The time effect inherent in this dualism causes allocational distortions of unknown magnitude. It is modeled employing effective tax rates. The extent of the divergence is determined empirically, using German cross-sectional data from the 2004 wave of the Socio-Economic Panel. The uneven distribution of this advantage across differently educated brackets of society is uncovered. The paper concludes with proposals to remedy the situation and a tentative endorsement of the Dual Income Tax.
Keywords: H21; H24; J24; J31; 330; Comprehensive Income Tax; Dual Income Tax; Effective Tax Rates; Wage Equation; Duale Einkommensteuer; Lohnsteuer; Einkommensteuer; Steuerbelastung; Steuerinzidenz; Humankapital; Deutschland